2013
DOI: 10.1038/nrgastro.2013.87
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNAs in liver disease

Abstract: Small, noncoding microRNAs (miRNAs) regulate diverse biological functions in the liver and increasing evidence suggests that they have a role in liver pathology. This Review summarizes advances in the field of miRNAs in liver diseases, inflammation and cirrhosis. MicroRNA-122, the most abundant miRNA in hepatocytes, has well-defined roles in HCV replication, and data indicate that it also serves as a viable therapeutic target. The role of miR-122 is also emerging in other liver diseases. Ample evidence exists … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
474
0
11

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 544 publications
(495 citation statements)
references
References 139 publications
10
474
0
11
Order By: Relevance
“…In line with our findings, a recent study [19] showed that 3 serum miRNAs, including let-7f, could separate HBV-HCC cases from controls. MiR-122, the most abundant liver-specific miRNA, is considered a suppressor of cell proliferation and malignant transformation of hepatocytes with remarkable tumor inhibition activity [32][33][34]. Interestingly, although downregulation of miR-122 was frequently reported in the HCC tumor tissues [2,34,35], Qi et al [36] showed that miR-122 in serum was elevated in HCC patients and markedly reduced in post-operative serum samples, which is consistent with the observation in our study.…”
Section: Discussionsupporting
confidence: 81%
“…In line with our findings, a recent study [19] showed that 3 serum miRNAs, including let-7f, could separate HBV-HCC cases from controls. MiR-122, the most abundant liver-specific miRNA, is considered a suppressor of cell proliferation and malignant transformation of hepatocytes with remarkable tumor inhibition activity [32][33][34]. Interestingly, although downregulation of miR-122 was frequently reported in the HCC tumor tissues [2,34,35], Qi et al [36] showed that miR-122 in serum was elevated in HCC patients and markedly reduced in post-operative serum samples, which is consistent with the observation in our study.…”
Section: Discussionsupporting
confidence: 81%
“…9,10 The sequence between mmu-miR-29a and hsa-miR29a was conserved across species (http://www.mirbase.org). We evaluated the ability of miR-29a to improve liver fibrosis using CCl 4 and TAA models established in Figure 1.…”
Section: Controlling Liver Fibrosis By Administering Mir-29amentioning
confidence: 99%
“…7 Aberrant expression of miRNA is associated with the progression of liver fibrosis. [8][9][10] For example, the expression of miR-132 and the miR-29 family (miR-29a, miR29b, and miR-29c) is significantly underexpressed in fibrotic livers, as demonstrated in human liver cirrhosis and in liver injury models induced by bile duct ligation and carbon tetrachloride (CCl 4 ) in mice. Downregulation of these miRNAs can modify the activity of HSCs.…”
Section: Introductionmentioning
confidence: 99%
“…The data presented herein support these findings, demonstrating the importance of inflammasomes and IL-1b release in the process of IRI. Other known data, such as cold ischemia time, warm ischemia time, and other specific donor conditions, cannot be ignored and are described widely [24,25]. Nonetheless, the different clinical outcomes of IRI and the different clinical presentation, can be, at least partially, attributed to different gene expression of IL-1b in donor livers, leading to a more significant inflammatory process during IRI in OLT [26,27].…”
Section: Discussionmentioning
confidence: 99%